Eksplorasi Etnomatematika pada Tradisi Saprahan Etnis Melayu Sambas dan Pengintegrasiannya dalam Pembelajaran Matematika Sekolah Dasar - Oktapiani, Metha; Bistari, Bistari; Salimi, Asmayani (AS-SABIQUN, 2024)
This study focuses on ethnomathematics in the Sambas Malay ethnic Saprahan tradition which aims to answer three questions: (1) Describe the mathematical fundamental activities in the Sambas Malay ethnic saprahan tradition, (2) Tools used in the Sambas Malay ethnic saprahan tradition related to mathematical concepts, (3) Describe the integration of ethnomathematics in the Sambas Malay ethnic saprahan tradition in elementary school mathematics learning. The method used is a qualitative research method in the form of ethnography. Researchers as the main instrument that plays a role in collecting data through interviews, observations and documentation. The data validity technique uses source triangulation and triangulation techniques. The results of this study show that there is ethnomathematics in the Saprahan tradition of the Sambas Malay ethnicity. In counting activities there is the concept of counting operations, measuring activities (measuring) there is the concept of measuring and flat building, locating activities there are the concepts of addition and flat building and inactivity, designing activities there are the concepts of counting and flat building operations, and explaining activities there are the concepts of counting and flat building operations. The concepts of elementary school mathematics in the tradition of Saprahan Malay Sambas can be developed by designing a suitable learning tool such as evaluation questions so as to provide new innovations in mathematics learning in schools.